2002
DOI: 10.1111/j.1432-2277.2002.tb00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential protocol biopsies from renal transplant recipients show an increasing expression of active TGF beta

Abstract: Chronic allograft nephropathy (CAN) is a major cause of graft loss after renal transplantation. Implicated in the pathogenesis of this complication is overproduction of the cytokine transforming growth factor beta (TGF β). In this study we measured changes in CAN's expression in stable patients early after transplantation, and studied links with established risk factors for CAN, such as delayed graft function, acute rejection, and cyclosporine exposure. We took biopsies from 40 renal allografts at time of tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…TGF‐β expression is induced in renal tissue by CyA in heart transplant recipients (29). In the absence of specific data in heart and lung transplant patients, extrapolation from studies involving protocol biopsies in kidney recipients suggests that renal expression of TGF‐β is similar in patients regardless of whether they are receiving CyA or Tac as their calcineurin inhibitor (30).…”
Section: Calcineurin Inhibition and Nephrotoxicitymentioning
confidence: 99%
“…TGF‐β expression is induced in renal tissue by CyA in heart transplant recipients (29). In the absence of specific data in heart and lung transplant patients, extrapolation from studies involving protocol biopsies in kidney recipients suggests that renal expression of TGF‐β is similar in patients regardless of whether they are receiving CyA or Tac as their calcineurin inhibitor (30).…”
Section: Calcineurin Inhibition and Nephrotoxicitymentioning
confidence: 99%
“…Interestingly, intra‐renal expression of TGF‐ β 1 was enhanced with both ciclosporin and tacrolimus therapy (Bicknell et al 2000, Jain et al 2002, Khanna et al 2002). However, quantitative analysis of the comparative levels of TGF‐ β 1 in biopsies from ciclosporin and tacrolimus‐treated patients have not revealed consistent results (Bicknell 2000, Mohammed et al 2000, Jain 2002, Khanna et al 2002). Furthermore, there are differences between the expression of latent TGF‐ β 1 and active TGF‐ β 1 which might be pathologically important (Mohammed et al 2000).…”
mentioning
confidence: 99%
“…Tacrolimus seems to have effects similar to ciclosporin in terms of stimulating TGF-b1 synthesis and secretion in lymphoid and non-lymphoid tissues albeit through different biochemical mechanisms (Han et al 1995, Khanna et al 1999. Interestingly, intra-renal expression of TGF-b1 was enhanced with both ciclosporin and tacrolimus therapy (Bicknell et al 2000, Jain et al 2002, Khanna et al 2002. However, quantitative analysis of the comparative levels of TGF-b1 in biopsies from ciclosporin and tacrolimustreated patients have not revealed consistent results (Bicknell 2000, Mohammed et al 2000, Jain 2002, Khanna et al 2002.…”
mentioning
confidence: 99%
“…On the other hand, exposure of CD8 cells to bioactive TGF‐β subsequent to their progression to effector status induces expression of CD103 without compromising effector function (39). An additional factor to be considered is that rejecting renal allografts are associated with exceptionally high levels of TGF‐β (54–56). Moreover, TGF‐β activity is not normally systemic, but rather is localized to peripheral inflammatory sites (51).…”
Section: Regulation Of Cd103 Expression By Cd8‐effector Populationsmentioning
confidence: 99%
“…An additional factor that limits the involvement of CD103 + CD8 + effectors is the availability of local TGF‐β activity. Rejecting renal allografts are associated with high levels of TGF‐β (54,55), and it is therefore possible that the renal environment is relatively unique in the capacity to induce CD103 expression by graft‐infiltrating CD8‐effector populations. In this regard, it is important to note that although we have reported that CD103 plays a critical role in rejection of pancreatic islet allografts (49), grafts in this study were transplanted into the renal subcapsular site, and it remains to be determined if CD103 plays an analogous role in destruction of islet grafts transplanted via the clinically relevant route (intraportally) or, for that matter, in vascularized renal allografts.…”
Section: Outstanding Issuesmentioning
confidence: 99%